NO and ABA Interaction Regulates Tuber Dormancy and Sprouting in Potato - Wang, Zhike; Ma, Rui; Zhao, Mengshi; Wang, Fangfang; Zhang, Ning; Si, Huanjun (Frontiers in Plant Science, 2020)
In plants, nitric oxide synthase (NOS)-like or nitrate reductase (NR) produces nitric oxide (NO), which is involved in releasing seed dormancy. However, its mechanism of effect in potato remains unclear. In this study, the exogenous NO donor, spraying 40 mM sodium nitroprusside (SNP) quickly broke tuber dormancy and efficiently promoted tuber sprouting, whereas 2-(4-carboxyphenyl)-4,4,5,5-tetramethylimidazoli- ne-1-oxyl-3-oxide (c-PTIO), a NO scavenger, repressed the influence of NO on tuber sprouting. Compared with the control (distilled water), SNP treatment led to a rapid increase in the NO content after 6 h and a decreased abscisic acid (ABA) content at 12 and 24 h. c-PTIO treatment significantly inhibited the increase in NO levels and increased ABA production. In addition, NG-nitro-L-arginine methyl ester (L-NAME), an NOS inhibitor, clearly inhibited the NOS-like activity, while tungstate, an NR inhibitor, inhibited the NR activity. Furthermore, NO promoted the expression of a gene involved in ABA catabolism (StCYP707A1, encoding ABA 8'-hydroxylase) and inhibited the expression of a gene involved in ABA biosynthesis gene (StNCED1, encoding 9-cis-epoxycarotenoid dioxygenase), thereby decreasing the ABA content, disrupting the balance between ABA and gibberellin acid (GA), and ultimately inducing dormancy release and tuber sprouting. The obtained results demonstrate that NOS- or NR-generated NO controls potato tuber dormancy release and sprouting via ABA metabolism and signaling in tuber buds.